CORPORATE SOCIAL RESPONSIBILITY AND BUSINESS PERFORMANCE: EVIDENCE FROM MALAYSIA OIL AND GAS COMPANIES - Aseh, Khairi; Kenny, Kamal (Archives of Business Research, 2020)
This work aims to explore the relationship between Corporate Social Responsibility (CSR) and financial performance in the energy sector for publicly traded companies. Due to their size, environmental implications, and the operational risks associated with energy production, the energy sector has a unique role to play with worldwide CSR efforts. Earlier research on the relationship between CSR engagement and financial performance has been conducted in various contexts. However, the results of these investigations have been mixed, with some positive CSR-performance relationships, while in other studies, research is either non-existent or marginal. The question of research for this research thus addresses a considerable gap in understanding this topic in the contextualization of the energy sector through an analysis of the relationship between CSR and firm performance. A series of three financial parameters – asset return, equity return, and EBITDA – were the dependent variable. In this study, the population who are presently working in a company of the energy sector in Malaysia examines the sampling methodology. There is a total of 30 listed companies, which were in the "Energy" sector, based on Bursa Malaysia's official websites. For the subsection, two categories are included, namely: (1) Energy, Equipment, and Gas, and (2) Oil & Gas. The random selection will include two companies from each subcategory from the complete list. In detail, 100 respondents from each company will be selected randomly for the study.